Peran Mata Kuliah Etika Profesi Keguruan dalam Pembentukan Karakter dan Praktik Profesional Mahasiswa Calon Guru di Indonesia - Bartolomeus Marulitua Simanjorang; Lennai Situmorang; Tengku Salsabila; Naulita Panggabean; Sri Yunita (Departement of Mathematics Education, 2024)
Education has a crucial role in forming individual character and morality, and the role of teachers as educational agents is very important in this process. This research method is a qualitative research method with a library approach, namely a research approach that uses written or literary sources of information, whether from books, journal articles, magazines and other sources as a basis for gaining an in-depth understanding of the role of the Teaching Professional Ethics course in character formation. and Professional Practices of Prospective Teacher Students in Indonesia. By better understanding its impact, we can identify learning strategies that are more effective and relevant to local contexts, thereby improving the quality of teacher education and, in turn, the quality of national education as a whole.